Early Antiretroviral Therapy Initiation and Mortality Among Infants Diagnosed With HIV in the First 12 Weeks of Life: Experiences From Kinshasa, DR Congo and Blantyre, Malawi. Issue 7 (July 2017) - Sheahan, Anna; Feinstein, Lydia; Dube, Queen; Edmonds, Andrew; Chirambo, Chawanangwa Mahebere; Smith, Emily; Behets, Frieda; Heyderman, Robert; Van Rie, Annelies
Abstract : Background: Based on clinical trial results, the World Health Organization recommends infant HIV testing at age 4–6 weeks and immediate antiretroviral therapy (ART) initiation in all HIV-infected infants. Little is known about the outcomes of HIV-infected infants diagnosed with HIV in the first weeks of life in resource-limited settings. We assessed ART initiation and mortality in the first year of life among infants diagnosed with HIV by 12 weeks of age. Methods: Cohort of HIV-infected infants in Kinshasa and Blantyre diagnosed before 12 weeks to estimate 12-month cumulative incidences of ART initiation and mortality, accounting for competing risks. Multivariate models were used to estimate associations between infant characteristics and timing of ART initiation. Results: One hundred and twenty-one infants were diagnosed at a median age of 7 weeks (interquartile range, 6–8). The cumulative incidence of ART initiation was 46% [95% confidence interval (CI), 36%, 55%] at 6 months and 70% (95% CI 60%, 78%) at 12 months. Only age at HIV diagnosis was associated with ART initiation by age 6 months, with a subdistribution hazard ratio of 0.70 (95% CI 0.52, 0.91) for each week increase in age at DNA polymerase chain reaction test. The 12-month cumulative incidence of mortality was 20% (95% CI 13%, 28%). Conclusions: Despite early diagnosis of HIV, ART initiation was slow and mortality remained high, underscoring the complexity in translating clinical trial findings and World Health Organization's guidance into real-life practice. Novel and creative health system interventions will be required to ensure that all HIV-infected infants achieve optimal treatment outcomes under routine care settings.